Proceedings of the Evaluation and Assessment on Software Engineering 2019
DOI: 10.1145/3319008.3319020
|View full text |Cite
|
Sign up to set email alerts
|

A Self-assessment Instrument for Assessing Test Automation Maturity

Abstract: Päivi Raulamo-Jurvanen M3S, ITEE, Test automation is important in the software industry but selfassessment instruments for assessing its maturity are not sufficient. The two objectives of this study are to synthesize what an organization should focus to assess its test automation; develop a self-assessment instrument (a survey) for assessing test automation maturity and scientifically evaluate it. We carried out the study in four stages. First, a literature review of 25 sources was conducted. Second, the initi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 38 publications
(38 reference statements)
0
16
0
Order By: Relevance
“…Our finding is consistent with findings made by prior scholars [27,35,28], who reported that better product quality can be achieved after adopting certain standard best practices for test automation maturity improvement in the CI context. However, our study examined a boarder range of standard best practices, as it was based on extensive literature reviews for standard best practices of test automation in our early studies [16,13].…”
Section: Summary and Discussion Of Study Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our finding is consistent with findings made by prior scholars [27,35,28], who reported that better product quality can be achieved after adopting certain standard best practices for test automation maturity improvement in the CI context. However, our study examined a boarder range of standard best practices, as it was based on extensive literature reviews for standard best practices of test automation in our early studies [16,13].…”
Section: Summary and Discussion Of Study Findingsmentioning
confidence: 99%
“…Their findings were based on authors' experience. Many standard test automation best practices in the literature were not included, e.g., prioritizing important automated tests for execution, providing enough resources, and using the right test automation metrics to measure test automation performance [16]. To sum up, our empirical study can complement prior studies and make the novelty from the following aspects:…”
Section: Test Automaton Maturity; Release Cycle; Product Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…While designing the data analysis for each round, we primarily followed the content validity index (CVI) method, which is the common method for this purpose (Bhatti & Ahsan, 2017), as guided by (Polit & Beck, 2006). The popularity of CVI is not only limited to educational, psychological, or nursing research, but also to other disciplines or research areas, such as researches in software engineering and information systems (Bhatti & Ahsan, 2017;Yilmaz et al, 2017;Wang et al, 2019). In this study, two quantities were calculated (Polit & Beck, 2006): 1.…”
Section: Rounds Of Content Validitymentioning
confidence: 99%